THE EFFECT THE EFFECT OF GARGLING WITH BOILED WATER OF ELEPHANT GINGER (ZINGIBER OFFICINALE VAR. OFFICINARUM) ON DENTAL PLAQUE IN CLASS X STUDENTS OF MADRASAH ALIYAH MIFTAHUL KHAIRIYAH BANJAR - fitriah, Fitriah; Nurwati, Bunga; Sabatul Habibah, Siti; Amperawati, Metty (Poltekkes Kemenkes Banjarmasin, 2025)
Ginger has benefits to reduce the development of dental plaque because it has antibacterial and anti-inflammatory properties. Active compounds in elephant ginger, such as gingerol, shogaol, and zingerone, can inhibit the growth of plaque-causing bacteria. Using elephant ginger solution as a mouthwash can help reduce plaque accumulation on the surface of the teeth. This study aims to determine the Effect of Gargling with Boiled Water of Elephant Ginger (Zingiber Officinale Var. Officinarum) on Dental Plaque in Class X Students of Madrasah Aliyah Miftahul Khairiyah, Banjar Regency. This type of research is analytical with quasi-experimental using the One Group Pretest-Posttest design. The sampling technique used Total Sampling with a sample size is 46 students. Data analysis using Paired Sample T-test. The results of this study obtained plaque on students before garfling with boiled water elephant ginger is 2,124. While the plaque after gargling with boiled water of elephant ginger is 1,520. Based on the results of statistical analysis with paired sample T-Test, it produces ???? = 0.000 so that it is smaller than α = 0.05. In conclusion, there is an effect of gargling with boiled water of elephant ginger (Zingiber Officinale Var. Officinarum) on dental plaque in class X students of Madrasah Aliyah Miftahul Khairiyah Banjar Regency. It is recommended for all students to be able to use elephant ginger as an alternative mouthwash to help reduce plaque on teeth.